2016
DOI: 10.1021/acs.nanolett.6b00053
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Charge Carrier Separation Dominates the Photoluminescence Decay Dynamics of Colloidal CdSe Nanoplatelets

Abstract: Luminescent colloidal CdSe nanoplatelets with atomically defined thicknesses have recently been developed, and their potential for various applications has been shown. To understand their special properties, experiments have until now focused on the relatively short time scales of at most a few nanoseconds. Here, we measure the photoluminescence decay dynamics of colloidal nanoplatelets on time scales up to tens of microseconds. The excited state dynamics are found to be dominated by the slow (∼μs) dynamics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
216
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(243 citation statements)
references
References 44 publications
(214 reference statements)
26
216
0
1
Order By: Relevance
“…NPLs or colloidal quantum wells have received enormous research interest since their thickness can be controlled with atomic precision and NPLs can exhibit thickness-tunable emission [18,19,20,21,22]. In 2006, Joo et al reported the first CdSe nanoribbons/NPLs with a wurtzite structure via low-temperature solution-phase synthesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…NPLs or colloidal quantum wells have received enormous research interest since their thickness can be controlled with atomic precision and NPLs can exhibit thickness-tunable emission [18,19,20,21,22]. In 2006, Joo et al reported the first CdSe nanoribbons/NPLs with a wurtzite structure via low-temperature solution-phase synthesis [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some NCs have a high quantum efficiency (near 100 %), while others have a quantum efficiency near 0 %. The two subpopulations in a NC ensemble are also known as the “bright fraction” and the “dark fraction” [251256] (see Fig. 9).…”
Section: Excited-state Dynamics In Semiconductor Nanocrystalsmentioning
confidence: 99%
“…The power-law exponents are around 1.5 for most NCs, and independent or nearly independent of temperature [276], excitation intensity [276], and nature of the excitation laser (continuous wave or pulsed) [296]. Interestingly, the band-edge emission of semiconductor NCs contains a slow “delayed” component with power-law statistics, that extends over time scales from nanoseconds up to (at least) milliseconds [240, 256, 297] (Fig. 10e).…”
Section: Excited-state Dynamics In Semiconductor Nanocrystalsmentioning
confidence: 99%
“…Some NCs have a high quantum efficiency (near 100 %), while others have a quantum efficiency near 0 %. The two subpopulations in a NC ensemble are also known as the ''bright fraction'' and the ''dark fraction'' [251][252][253][254][255][256] (see Fig. 9).…”
Section: Radiative Decay In Semiconductor Nanocrystals: Ns To Ls Timementioning
confidence: 99%
“…The power-law exponents are around 1.5 for most NCs, and independent or nearly independent of temperature [276], excitation intensity [276], and nature of the excitation laser (continuous wave or pulsed) [296]. Interestingly, the band-edge emission of semiconductor NCs contains a slow ''delayed'' component with power-law statistics, that extends over time scales from nanoseconds up to (at least) milliseconds [240,256,297] (Fig. 10e).…”
Section: Blinking Dynamics On Ms Timescales and Slowermentioning
confidence: 99%